2004
DOI: 10.1103/physrevd.69.063514
|View full text |Cite
|
Sign up to set email alerts
|

Kasner and mixmaster behavior in universes with equation of statew>~1

Abstract: We consider cosmological models with a scalar field with equation of state w ≥ 1 that contract towards a big crunch singularity, as in recent cyclic and ekpyrotic scenarios. We show that chaotic mixmaster oscillations due to anisotropy and curvature are suppressed, and the contraction is described by a homogeneous and isotropic Friedmann equation if w > 1. We generalize the results to theories where the scalar field couples to p-forms and show that there exists a finite value of w, depending on the p-forms, su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
335
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(342 citation statements)
references
References 28 publications
(55 reference statements)
5
335
1
1
Order By: Relevance
“…Contrary to Lemaître's model, the cyclic universe has an added component, a phase of ekpyrotic contraction [335,336], that bounded. In [151], Lehners et al envisioned reheating in the cylic scenario as occurring via the transfer of some kinetic energy between branes.…”
Section: Avoidance Of Relicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to Lemaître's model, the cyclic universe has an added component, a phase of ekpyrotic contraction [335,336], that bounded. In [151], Lehners et al envisioned reheating in the cylic scenario as occurring via the transfer of some kinetic energy between branes.…”
Section: Avoidance Of Relicsmentioning
confidence: 99%
“…Thus, distortions and anisotropies are expected to be strongly amplified during contraction in cyclic or ekpyrotic cosmologies. However, prior analytic [335] and numerical studies [336] …”
Section: Bkl Instabilitymentioning
confidence: 99%
“…Nevertheless, such possibilities have been seriously considered [93], and we do not rule them out completely, at least not in the very early Universe. In short, it is possible to keep the brane action positive everywhere, but only by means of choosing rather extreme parameter values.…”
Section: Brane Pair Production: Constant Eos Parametermentioning
confidence: 99%
“…Other aspects of the cyclic and ekpyrotic models have been criticized [11] (see [12] for replies), and some have argued that a bounce is impossible altogether [13]. While the consistency of a bounce remains to be proven, recent work has shown that the traditional hazard of chaotic mixmaster behavior is strongly suppressed in the contracting phase of the cyclic model [14]. The metric perturbations exhibit ultralocal behavior in which anisotropies remain small, right up to a few Planck times before the bounce.…”
Section: Introductionmentioning
confidence: 99%